The economics of public spending - Miles, David; Myles, Gareth D.; Preston, Ian (Oxford ; New York : Oxford University Press, 2003)
The Economics of Public Spending investigates the extent of government involvement in the economy, details its rationale, and traces its historical economists who specialize in that field. The chapters describe both the data on public expenditure and the theory relevant to understanding the policy issues. An extended introduction investigates the overall role of the public sector and discusses the general theory of public expenditure.
Includes bibliographical references and index.
rpm 21/10/13, gau 06/06/14
Loans
Keywords: Expenditures, Public; Great Britain